Gender and digital technologies: which factors keep women away from programming and IT services? - Yansen, Guillermina (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2020)
This text aims to systematize the literature that addresses the relationship between gender and IT activities in recent years. More specifically, that which in different ways helps to answer the question about the factors that distance women from IT work activities, prototypically located in the software and IT services sector in Argentina. Although the question is, at first glance, quite limited, answering it leads to the review of a vast literature. We dedicate the opening section, first, to delimiting the object, by defining informatics (or IT) activities; and second, to highlighting the importance of this problem, which implies reviewing the current situation of the level of participation of women in computer activities, especially, but not only, at the national level, by showing data on the labor market and higher education. The second section specifies the ordering criteria of the literature. Then, each sub-section gives an account of the literature that has made contributions for each of the identified stages. Finally, we draw some conclusions.
Keywords: Argentina; education; software; trajectories; work